Psychometric properties of the Marlowe-Crowne social desirability scale in Peruvian teachers - Burga León, Andrés Alberto (2017)
The objective of the research was to gather evidence of the psychometric properties of the scores derived from the Marlowe–Crowne Social Desirability Scale applied to a population of 28 972 second-grade elementary school teachers in Peru, considering different strata, such as management type (public sector 74% and private sector 26%) and geographic location (urban 65% and rural 35%). Psychometric analyses were developed in two samples of 5000 cases each, with similar characteristics to those of the study population. In addition, social desirability of the teachers was described and compared. The results allowed to gather validity evidence linked to the internal structure of the instrument by applying exploratory and confirmatory factor analyses that supported the unidimensionality of the instrument. In order to analyze the reliability of the instrument, measurement models were assessed, with the congeneric model being the best option to characterize the items. Therefore, reliability was assessed using omega coefficients that reached values between .83 and .87. Additionally, confidence intervals, standard errors of measurement, and scales based on percentile ranks were included in the research. To compare social desirability scores by stratum, the instrument invariance was analyzed and no significant statistical differences were found. Doi: https://doi.org/10.24265/liberabit.2017.v23n2.03